Construction and calibration of a bar weighing lysimeter - Daiane Cinque Mariano; Rogério Teixeira Faria; Paulo Sergio Lourenço de Freitas; Bruno Patias Lena; Andre Luiz Johann (Acta Scientiarum. Agronomy, 2015)
Generally, standard lysimeters include a lever-load cell scale, which has become expensive compared to new electronic equipment available for experimental purposes. Currently, lysimeters containing weighing bars with up to 4 load cells are economically feasible. This goal of this study was to present the construction and calibration of four weighing lysimeters built using two rectangular tanks, with a surface area of 1.35 m2 (1 m by 1.35 m) and a depth of 1.5 m, loaded on two weighing bars. Each bar had two high accuracy loading cells connected to a junction box and a datalogger by a coaxial cable. Calibration of each lysimeter was performed after field installation. The results showed a linear response (R2 > 0.9999) of electric signal (mV) to mass increase or decrease (kg) with minimum hysteresis. The mean absolute error of the mass estimate (0.0245 to 0.2844 equivalent-mm) and a Willmott index between the observed and estimated data (d = 1.0000) indicate the high precision of the new equipment. The results allow concluding that the lysimeters in this study are appropriate for estimating evapotranspiration and other components of soil water balance.